2014
DOI: 10.1128/aem.03856-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Mechanisms Responsible for Differences between Nitrogen Requirements of Saccharomyces cerevisiae Wine Yeasts in Alcoholic Fermentation

Abstract: Nitrogen is an essential nutrient for Saccharomyces cerevisiae wine yeasts during alcoholic fermentation, and its abundance determines the fermentation rate and duration. The capacity to ferment under conditions of nitrogen deficiency differs between yeasts. A characterization of the nitrogen requirements of a set of 23 strains revealed large differences in their fermentative performances under nitrogen deficiency, and these differences reflect the nitrogen requirements of the strains. We selected and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 39 publications
1
43
1
Order By: Relevance
“…The rate of protein synthesis is much lower in the stationary phase than during exponential growth, although it still remains moderately active during this phase. Indeed, the inhibition of protein synthesis by cycloheximide is associated with a large decrease of fermentation rate consistent with the requirement of protein synthesis to sustain fermentation flux (Brice et al 2014a;Salmon 1989). The total amount of protein exhibits only minor changes upon starvation through substantial remodeling of the proteome (Breker et al 2013;Rossignol et al 2009).…”
Section: Effect Of Starvation On Protein Fate and Amino Acid Homeostasismentioning
confidence: 96%
See 4 more Smart Citations
“…The rate of protein synthesis is much lower in the stationary phase than during exponential growth, although it still remains moderately active during this phase. Indeed, the inhibition of protein synthesis by cycloheximide is associated with a large decrease of fermentation rate consistent with the requirement of protein synthesis to sustain fermentation flux (Brice et al 2014a;Salmon 1989). The total amount of protein exhibits only minor changes upon starvation through substantial remodeling of the proteome (Breker et al 2013;Rossignol et al 2009).…”
Section: Effect Of Starvation On Protein Fate and Amino Acid Homeostasismentioning
confidence: 96%
“…A specific method, based on the measurement of the nitrogen supply required to keep the fermentation rate constant in the stationary phase (constant rate fermentation method), has been proposed to quantify the nitrogen needs of yeast strains (Julien et al 2000;Manginot et al 1997;Manginot et al 1998). The molecular characterization of strains with different nitrogen requirements has revealed differences in gene expression between strains; those with high nitrogen requirements overexpress stress genes, whereas strains with low nitrogen needs overexpress biosynthetic genes (Brice et al 2014a). Through a QTL approach, Brice et al (2014b) identified allelic variations in several genes that affect nitrogen requirement.…”
Section: Effect Of Nitrogen Content On Fermentation Kineticsmentioning
confidence: 98%
See 3 more Smart Citations